Biology and pharmacological inhibition of homeodomain-interacting protein kinases - Štefek, Adam; Paruch, Kamil (Frontiers in Chemical Biology, 2025)
Homeodomain-interacting protein kinases (HIPKs) represent a relatively underexplored sub-family of serine/threonine protein kinases. However, the recently published studies point to the role of HIPKs in the developmental biology and etiology of pathological states, in particular cancer, and potential therapeutic applications of targeting this kinase family. This review summarizes the biology of HIPKs and their heretofore published small-molecule inhibitors.